Hubungan Antara Minat Belajar Dengan Prestasi Belajar Siswa Pada Mata Pelajaran Aqidah Akhlak Di MA Muhammadiyah 1 Paciran - Abdul Khair, Nashrudin (STAI Muhammadiyah Paciran Lamongan, 2025)
This study aims to determine the positive impact of learning interest on student achievement in the Aqidah Akhlak subject for class XI MIPA 2 at MA Muhammadiyah 1 Paciran. The research uses Parametric Statistical Analysis with a quantitative approach, involving 20 respondents. The collected data were analyzed using parametric statistical techniques. The hypothesis testing of this research shows that: 1) The influence of learning interest on student achievement in the Aqidah Akhlak subject for class XI MIPA 2 at MA Muhammadiyah 1 Paciran is moderate. This is indicated by the frequency percentage of learning interest in the Aqidah Akhlak subject for class XI MIPA 2, which is highest at 55%. 2) The student achievement in the Aqidah Akhlak subject for class XI MIPA 2 at MA Muhammadiyah 1 Paciran is good. This is shown by the percentage of students who scored above the Minimum Passing Criterion (KKM), which reached 55%, specifically in the interval above 82. 3) The result of the hypothesis testing shows that the rtabel value for the degrees of freedom (df) = 20-2 = 18 with a 5% significance level is 0.443, while the rhitung value is 0.605. Since rhitung is greater than rtabel, it means there is an influence between learning interest (X) and the variable of learning achievement in the Aqidah Akhlak subject (Y).